2018
DOI: 10.1002/bkcs.11636
|View full text |Cite
|
Sign up to set email alerts
|

Developing Low Fouling on PET Film via Surface‐initiated ARGET ATRP of Carboxybetaine under Air Condition

Abstract: Poly(ethylene terephthalate) (PET) is one of the most popular thermoplastics for daily use and finds application in packaging products for food and beverage storage, as well as textile materials for clothing. 1 The important features of PET, such as shatterproof nature, high strength to weight ratio, low cost, and recyclability make it feasible for use at the industrial scale for the aforementioned products. 2,3 In addition, PET shows flexible processability as well as moderate mechanical durance and physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…For the PTFEA brushes, X‐ray photoelectron spectroscopy (XPS) revealed the emergence of the characteristic fluorine F1s peak at BE F1s = 689.0 eV, further confirming the successful preparation of the brush coating (Figure S3C, Supporting Information). [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…For the PTFEA brushes, X‐ray photoelectron spectroscopy (XPS) revealed the emergence of the characteristic fluorine F1s peak at BE F1s = 689.0 eV, further confirming the successful preparation of the brush coating (Figure S3C, Supporting Information). [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, its reaction conditions should be carefully applied under low temperatures, limiting their practical usage for the surface coating. In this sense, we introduced an aryl azide-based initiator (ABI) that can be feasibly immobilized on a TA-Fe III film when irradiated with UV light. The synthesized ABI can be classified into three components, namely, the head, spacer, and terminal initiator groups. Perfluorophenylazide (PFPA) was selected as a head group because the photolysis of PFPA can generate a reactive nitrene group that can functionalize the sp 2 -rich hydrocarbon network of TA.…”
Section: Resultsmentioning
confidence: 99%
“…Second, it has been reported that fluorine groups of the aromatic ring suppress the intramolecular ring expansion of nitrene, increasing the insertion/addition adducts with hydrocarbons, in this case, TA . On the basis of our previous report, the photochemical PFPA group was utilized to immobilize the biotin or ATRP initiator group in carbon-based materials, such as graphene, a cyclic olefin copolymer (COC), or polyethylene terephthalate (PET) . The head and terminal initiator groups were linked with short ethylene glycol to increase their overall solubility and flexibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Because of this regenerative catalytic cycle, ARGET ATRP needs no deoxygenating steps for the reaction solutions and it can be proceeded with a very low concentration of a Cu catalyst (at the level of several ppm) under ambient conditions. Along the same line with grafting-from approach, surface-initiated ARGET ATRP (SI-ARGET ATRP) has been successfully applied to a variety of applications including the preparation of low fouling surfaces, 20,21 development of the universal polymer grafting method to fabricate blood compatible surfaces, 22 and the preparation of biocompatible graphene nanosheets. 23 While SI-ARGET ATRP has been widely utilized to prepare functional coatings by grafting polymers from surfaces, there has been little study to investigate systematically the polymer grafting of various monomers over time using the same platform.…”
Section: Introductionmentioning
confidence: 99%